(untitled) (Agroindustria, Sociedad y Ambiente, 2018)
The purpose of the study was to generate an epistemological discussion about the paradigmatic theoretical link between educational coaching, the ontology of language (Echeverría, 1994) and social constructivism (Vygotsky, 1995, Piaget, 2001); in the context of advising students of Agroindustrial Engineering students. The work was framed in the interpretive paradigm, because it focused on the understanding of the theories consulted in terms of their applicability, in the development of the tutorials of degree work in the agro-industrial area. Once generated the epistemological discussion, it was concluded that educational coaching is an ideal alternative to promote the training of research engineers, motivated to research for the search of solutions to current problems in the framework of food security.